Determinants of Islamic Banking Profitability in Malaysia - Abduh, Muhamad; Idrees, Yameen (INSI Publications, 2013)
Islamic banks were experiencing tremendous growth by showing high profitability level and less affected by the financial turmoil. Thus, the objective of this paper is to investigate the impact of bank-specific as well as industry-specific and macroeconomic indicators upon Islamic banks profitability, particularly in Malaysia, for the period of 2006 to 2010. Using pooled regression analysis, and by taking 10 Islamic banks/windows, the result shows that the bank size is a vital importance in affecting its profitability. In addition, financial market development and market concentration has a significant positive impact in determining profitability. Finally, from the macro-economic variables, inflation has a significant positive impact on Islamic banks’profitability which shows the different nature between Islamic and conventional banks.